2013
DOI: 10.2134/jeq2012.0418
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Uncertainty Analysis for the Annual Phosphorus Loss Estimator Model

Abstract: Models are often used to predict phosphorus (P) loss from agricultural fields. Although it is commonly recognized that model predictions are inherently uncertain, few studies have addressed prediction uncertainties using P loss models. In this study we assessed the effect of model input error on predictions of annual P loss by the Annual P Loss Estimator (APLE) model. Our objectives were (i) to conduct a sensitivity analyses for all APLE input variables to determine which variables the model is most sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 38 publications
4
37
0
Order By: Relevance
“…For example, Moriasi et al (2016) determined the uncertainty of APEX-simulated annual runoff to be ±3% for a small watershed in Ohio. Bolster et al (2014) estimated the uncertainty of P predictions by the Annual P Loss Estimator (APLE) model (Vadas et al, 2009) to be within 28% for a high uncertainty of input parameters. Thus, the differences between buffer effectiveness calculated with measured or simulated data (up to 8% for runoff and 3% for TP) were within the same range as or smaller than common uncertainty ranges associated with measured data and modeling results.…”
Section: Buffer Effectiveness Using Simulated Paired Watershed Approachmentioning
confidence: 99%
“…For example, Moriasi et al (2016) determined the uncertainty of APEX-simulated annual runoff to be ±3% for a small watershed in Ohio. Bolster et al (2014) estimated the uncertainty of P predictions by the Annual P Loss Estimator (APLE) model (Vadas et al, 2009) to be within 28% for a high uncertainty of input parameters. Thus, the differences between buffer effectiveness calculated with measured or simulated data (up to 8% for runoff and 3% for TP) were within the same range as or smaller than common uncertainty ranges associated with measured data and modeling results.…”
Section: Buffer Effectiveness Using Simulated Paired Watershed Approachmentioning
confidence: 99%
“…The sensitivity analyses approach used in this study follows those used in other AnnAGNPS modeling studies (Yuan et al, 2003;Das et al, 2008;Liu et al, 2008;Parker et al, 2008), with due recognition of some of the limitations of the one-at-a-time sensitivity measures for nonlinear models (Bolster and Vadas, 2013). The sensitivity approach taken herein was performed principally to descriptively document consistencies, or the lack thereof, with sensitive parameters in the literature to justify variable selection for model calibration/validation.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Sensitivity and uncertainty analysis done for APLE model using First Order Approximation (FOA) and Monte Carol Simulation (MCS) showed that the MCS was found better for its overall uncertainty analysis [21]. Therefore, in this study the MCS technique was employed after reducing the DP man component of equation 2 due to the absence of manure application on the study area.…”
Section: Model Sensitivity and Uncertainty Analysismentioning
confidence: 99%
“…To make the simulated output credible and the model prediction valid, the uncertainty analyses were performed using Monte Carlo simulation with an adequate number of simulations (i.e. 200000) by assuming a triangular distribution of uncertainty which gives better distribution of data sets [21]. The model prediction uncertainties were calculated using the same input data sets as of sensitivity analysis ( Table 5).…”
Section: Model Sensitivity and Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation